On modern poetry - Mazzoni, Guido 1967- (The Belknap Press of Harvard University Press, 2022)
"Guido Mazzoni tells the story of poetry's revolution in the modern age. The chief transformation was the rise of the lyric as it is now conceived: a genre in which a first-person speaker talks about itself. Mazzoni argues that modern poetry embodies the age of the individual and has wrought profound changes in the expectations of readers"--Provided by publisher.